2010
DOI: 10.1537/ase.090408
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobinopathies and glucose-6-phosphate dehydrogenase deficiency in a malaria endemic region of Manipur, northeast India

Abstract: This study deals with the screening of haemoglobinopathies and glucose-6-phosphate dehydrogenase (G6PD) deficiency among three population groups of Manipur, namely 302 Pangan (Manipuri Muslim), 300 Bamon (Manipuri Brahmin), and 111 Kabui (tribal) individuals. Blood samples were collected by finger prick method and were screened for abnormal haemoglobins by using the Naked Eye Single Tube Red Cell Osmotic Fragility Test. The male samples of Pangan (136), Bamon (127), and Kabui (51) were also screened for G6PD d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…19 A study conducted in Manipur in 2010 by Achoubi among the different communities found high prevalence among the Manipuri Muslims (21.32%) followed by the Brahmins (9.45%) and Kabui (7.84%). 20 In Mizoram also, a high prevalence of 17.5% was found in the population. 21 In this study, it has been seen that among the tea garden labourers 7.6% of them had G6PD deficiency.…”
Section: Discussionmentioning
confidence: 92%
“…19 A study conducted in Manipur in 2010 by Achoubi among the different communities found high prevalence among the Manipuri Muslims (21.32%) followed by the Brahmins (9.45%) and Kabui (7.84%). 20 In Mizoram also, a high prevalence of 17.5% was found in the population. 21 In this study, it has been seen that among the tea garden labourers 7.6% of them had G6PD deficiency.…”
Section: Discussionmentioning
confidence: 92%
“…Gene frequency was calculated by simple gene count method. Several reports regarding G6PD deficiency were published in several caste groups/tribes like Parsee [13], Muslim [20], Brahmin [21][22][23], Jat [22], Rajputs [18], Vatalya Prajapati [24], Nagas [25], Kharia [26], Bhuyan [26], Danguria tharu [27], Kabui [20], and so forth. The frequency is higher among the tribals than the caste populations [15].…”
Section: Methodsmentioning
confidence: 99%
“…These sickle genes are responsible and capable of protecting these tribals from deadly malaria [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In addition to the sickle cell gene, some other genes for red cell genetic disorders, such as Hb-C, β-thalassaemia, glucose-6-phosphate dehydrogenase (G-6-PD) deficiency, and blood groups are also found for genetic resistance to malaria in human populations [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. This current communication provides factual and scientific information about the origin of sickle cell genes in the context of natural selection and how these genes protect tribal individuals from malaria.…”
Section: Introductionmentioning
confidence: 99%